Disharmonisasi Hubungan Keluarga Menurut Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Afandi; Mohammad Imamin Na’im; Nurika Falah Ilmania (Fakultas Hukum Universitas Islam Malang, 2023)
Family is the smallest unit in social life which should be created on the basis of liking and loving one another. Marriage is a sacred process and cannot be avoided by every human being who wants to form a family based on law. However, not a few human marriages will go well as what is aspired to, namely forming a family that is sakinah, mawaddah and warohmah. The research method used in writing is normative juridical, using primary and secondary legal materials which are carried out using descriptive analysis. Disharmony in the perspective of Law Number 1 of 1974 concerning Marriage (Marriage Law) can occur due to influences from other internal and external aspects that can affect harmony in the household.